Visual problems among video display terminal (VDT) users in Nepal - Gauri Shankar Shrestha (Journal of Optometry, 2011)
Purpose: To evaluate visual problems, major symptoms, and their associations among VDT users in Nepal. Methods: Among 76 hospital attendees, assessment included visual acuity, retinoscopy, convergence, accommodation, fusional vergence and Schirmer's II. Subjects’ symptoms were recorded in the structured 5 point intensity scale questionnaire. Results: Mean age of subjects was 25.8 ± 5 years with 6.9 ± 2.6 hours/day of computer use. Ocular changes were reported in 92.1% of the total subjects. The common ocular change was accommodative infacility. The most common symptoms (p < 0.001) were tired eye and headache. Reduced tear secretion as indicated by Schirmer's test II was found to have a little role in manifesting the symptoms as indicated by regression coefficient. Conclusions: Accommodative infacility and tired eye were the most common abnormalities and symptom reported. Schirmer's test II was slightly correlated with some ocular, visual, and systemic symptoms.